Effect of oral health education based on COM-B model on improving the oral health behavior of preschool children - Navid Aghadavudi Jolfaei; Bahareh Tahani (Journal of Education and Health Promotion)
BACKGROUND: The responsibility of brushing teeth in preschool children lies with the parents. The aim of this study was to determine the effect of an educational package on brushing habits and gum health in children aged 4–6. MATERIALS AND METHODS: This clinical controlled trial was conducted in three kindergartens located in Isfahan during the 2022–2023. The educational intervention was designed and implemented based on the COM-B behavioral model. Group I received animation, an educational video, and reminders; group II just got educational video; and the control group received no intervention. Before and one month after the intervention, plaque index, and gingival index were recorded. To evaluate the impact of interventions on the children’s toothbrushing behavior, parents were given a toothbrushing checklist and a self-assessment COM-B checklist consisted of six questions based on the VAS index. Data were analyzed using SPSS (α = 0.05). RESULTS: Among the study participants (91 individuals), data from 62 individuals were finally completed. In intervention group I, COM-B scores were significantly increased in terms of motivation (14.4 ± 3.4 vs. 16.1 ± 3.3, P = 0.04) and capability (15 ± 3.3 vs. 16.9 ± 3.6, P = 0.03). Improvement in plaque index was more noticeable in intervention group I (11.2 ± 6.4 vs. 6.9 ± 2.3, P value < 0.001), especially in girls. Brushing at least once a day and the direct involvement of parents in brushing were improved significantly. The GI changed nonsignificantly. CONCLUSION: The designed oral health educational package was successful in improving the plaque index and some domains of COM-B among parents. This model might be promising to be used in kindergartens.